Matching of lateral cephalograms by means of similarity coefficients - Seliga Michelle E.; Freer Terence J.; Basford Kay E. (Sciendo, 1986)
This was a pilot study to establish the possible applications of taxonomic methods (taxonomy = study of the general principles of classification) to the identification of individuals. Similarity coefficients were calculated from data obtained from standardised orthodontic cephalograms and were used to identify individuals by a process of matching.